Evaluasi Proses Pembelajaran Pendidikan Agama Islam di SMK Muhammadiyah 4 Glenmore Kabupaten Banyuwangi - Afandi, Ahmad; Khaerudin, Khaerudin; Muammar, Muammar (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2024)
This article aims to find out the results of the evaluation and follow-up from the evaluation of the Islamic Religious Education learning process at Muhammadiyah Glenmore Vocational School with the CIPP Model developed by Stufflebeam. This research uses a qualitative approach and evaluative research type with the CIPP (Context, Input, Process and Product) evaluation model. The research data sources are school principals, PAI subject educators and student representatives. The main data from this research was obtained through descriptive analysis, with a data collection process through observation, interviews and documentation. Then the data was analyzed by data reduction, data presentation, and drawing conclusions. Based on the results of the research that has been carried out, the following results were obtained which were analyzed and adapted to the evaluation instrument for the implementation of national education standards. In the context evaluation by assessing aspects of curriculum components and program management planning, good results were obtained with a percentage score of 81.25%; In the input evaluation with an assessment in terms of procurement aspects, the condition of infrastructure and academic facilities for educators and students, a good percentage of 75% was obtained; In the process evaluation by assessing aspects of the equipment, learning process and teacher competency, good results were obtained with a percentage of 83.33; In product evaluation by assessing implementation aspects, the results of the assessment and competency of graduates obtained good results in the field with a percentage of 75%. These results show that the evaluation of the PAI learning process using the CIPP model at SMK Muhammadiyah 4 Glenmore is in the good category.